Using 5-Nitroimidazole Derivatives against Neglected Tropical Protozoan Diseases: Systematic Review - Micheel M. Vichi-Ramírez; Edgar López-López; Catalina Soriano-Correa; Carolina Barrientos-Salcedo (MDPI AG, 2024)
Neglected tropical diseases (NTDs) are a significant global health problem. Additionally, anti-protozoan treatments are toxic, and their therapeutic regimens require prolonged treatment times and high concentrations of the drugs. Additionally, multi-resistant protozoan strains represent an important global emergency that must be addressed. For these reasons, global efforts are being made to identify new drug candidates that are capable of combating these kinds of diseases. This systematic review shows that 5-nitroimidazole derivatives have been successfully used against neglected tropical protozoan diseases (NTPDs), with a specific focus on three diseases: malaria, leishmaniasis, and human trypanosomiasis. Some nitroimidazole derivatives have been repurposed, and an important group of new drugs is available for the treatment of NTPDs. Finally, we address 5-nitroimidazoles using chemoinformatics and medicinal chemistry tools to describe the most recent and promising 5-nitroimidazole derivatives associated with anti-protozoal activity using their published in vitro and in vivo data. We show that 5-nitroimidazoles offer a broader spectrum of activity against a variety of protozoal pathogens. More importantly, these compounds demonstrate a significantly reduced systemic toxicity compared to other nitroimidazoles. This makes them a more favorable option in the treatment of protozoal infections, particularly in scenarios where the patient's tolerance to drug side effects is a critical concern.